A case study of the collapse of the over-chamber reinforced concrete ceiling of a meal silo. (1st August 2019) - Bywalski, C.; Kamiński, M.
Highlights: Cohesive arching of the bulk material stored in silos. An extraordinary load state on the silo structure due to the arching. Failures or collapses of silos during arch clearance. Failure scenario of silo ceiling due to the arch clearance. Abstract: This paper discusses the failure of the over-chamber reinforced concrete ceiling of a cylindrical silo for storing extracted rapeseed meal. The failure resulted from the caving in of an arch formed in the chamber and the sliding down of the material column. Some factors contributing to the caking and arching of the cohesive materials stored in silos are identified. An analysis of the extraordinary loads during the autogenous or induced clearance of arches is made. Such loads are not taken into account by design standards. Attention was paid to the necessity of figuring these loads in the design (an own proposition was put forward); also, ways of preventing such impact or its limitation were pointed out. The direct cause and the indirect causes of the failure are determined. Design and utilization errors which contributed to the formation of the arch, the failure of the ceiling of silo and the compounding of the failure consequences are identified.